Analisis Strategi Pengembangan Karier PNS Pada Bagian Umum Setda Kabupaten Merauke - Bebena, Boy Sandy Alfredo; Batlajery, Semuel (Musamus University, Merauke Papua Indonesia., 2024)
This study used a qualitative research method using a descriptive research type. Data collection was carried out by observation, interview and documentation techniques. While the data analysis method used is data reduction, data presentation, and drawing conclusions. In this study, a credibility test was used to test the validity of the data by triangulating data sources. The purpose of this study was to determine the career development strategy of civil servants in the General Section of the Regional Secretariat of Merauke Regency. In obtaining research data, researchers interviewed 8 informants as samples using the sampling technique used was Snowball sampling. The results of the study found that of the four indicators of career development strategies for civil servants in the General Section of the Regional Secretariat of Merauke Regency, only indicators of guidance from leaders and indicators of education and training were quite good. While the promotion and mutation indicators have not been implemented properly. This is due to the lack of information about promotions and transfers to civil servants which have an impact on employee career development.